Exploration of quality control methods for regional COVID-19 nucleic acid detection laboratories - LOU Jiao, JIANG Lingli, WANG Yin, ZHOU Jing, HU Xiaobo, WANG Qing, et al (Zhenduanxue lilun yu shijian, 2022)
Objective: To explore the quality and safety of testing in the city′s regional medical laboratories for COVID-19 nucleic acid detection. Methods: To strengthen the quality control of the city′s medical laboratories for COVID-19 nucleic acid detection through monthly inspections, squatting inspections, emergency inspections, blind sample surveys, sample retention, and retesting. Results: Regional medical laboratories for COVID-19 nucleic acid detection were non-compliant in terms of personnel qualifications, business training, internal quality control, result judgement, retesting processes, report uploading, cleaning and disinfection, and medical waste disposal. The number of laboratories conducting COVID-19 nucleic acid testing gradually expanded from 29 at the beginning of the outbreak on March 18 to 98 on May 16, but the number of non-compliant laboratories did not increase significantly. The pass rate of the blind sample survey of the city′s medical testing laboratories ranged from 96.6% to 100.0%, and the concurrence rate between the results of the laboratory′s retained samples for retesting and the results of the retained testing facilities ranged from 98.3% to 100.0%. Conclusions: The quality of regional COVID-19 nucleic acid detection in the city is generally controllable, with no systematic quality problems. The quality control model with multiple measures is worthy of application in the quality control of regional COVID-19 nucleic acid detection.